آلية الاشتقاق الصرفي وصناعة المصطلح العلمي الحديث - لخضر، طرش (جامعة زيان عاشور الجلفة, 2022)
ارتبطت صناعة المصطلحات العلمية عند الدارسين المحدثين العرب أكثر ما ارتبطت بإيجاد مقابلات لمصطلحات أجنبية، وذلك باعتماد آليات متعددة، منها: الاشتقاق، والتركيب، والتعريب، والنحت، وأهم هذه الآليات وأيسرها الاشتقاق الصرفي، لكثرة أوزان اللغة العربية، وطواعية أبنيتها التصريفية، وإن كان التعويل عليه يكاد يكون مقصورا على الأعمال التي ترعاها المجامع اللغوية وبعض مؤسسات التعريب، وذلك بجنوح لفيف من المصطلحيين من أصحاب الاجتهادات الفردية إلى اعتماد آليات أخرى في وضع المصطلحات، بدون مبرر ولا ضوابط أحيانا، كالاقتراض اللغوي، والنحت. وهذه الورقة البحثية محاولة للفت الانتباه إلى أهمية آلية الاشتقاق الصرفي في إيجاد المصطلحات العلمية، وتسليط الضوء على طرق الاشتقاق المتبعة في بعض المنجزات المصطلحية العلمية الحديثة، وتبيين الفروق المنهجية بينها. The scientific terminology industry of Arab modern scholars has been most associated with the creation of interviews with foreign terminology, by adopting various mechanisms, including derivation, installation, arabization and sculpture, the most accessible of which is expletive derivation. The weights of the Arabic language, and the voluntary drainage of its buildings, although reliance on it is limited to work sponsored by linguistic communities and certain institutions of Arabism, and that's why there's a tendency from the two terms of individual jurisprudence to the adoption of other mechanisms in the development of terminology. Unjustified and sometimes uncontrolled, such as language borrowing, sculpture. This research paper is an attempt to draw attention to the importance of the pure derivative mechanism in the creation of scientific terminology. Highlighting the methods of derivation used in some recent scientific term achievements, and illustrating the methodological differences between them.
Keywords: المصطلحات العلمية -- اللغة العربية -- الاشتقاق -- علم الصرف